(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The financial market plays a crucial role in the economic system, providing a platform for the allocation of resources and the facilitation of trade in financial assets. This article delves into the theoretical foundations of the financial market, examining key concepts, mechanisms, and the interplay between various market participants. By exploring fundamental theories such as market efficiency, asset pricing, and financial intermediation, this paper aims to provide a comprehensive understanding of the financial market’s functioning and its implications for economic stability and growth.